6 - Government-driven land and Agrarian Reform Programmes in Post-Apartheid South Africa – a Brief History (1994-2021).: Roland Nkwain Ngam - Roland Nkwain Ngam (African Sociological Review, 2021)
South Africa is one of the most unequal countries in the world, a reality created by colonial and apartheid-era race-based property laws which transferred 80% of the land to whites who make up only 10% of the population, while blacks had to make do with the remaining 20% (Presidential Advisory Panel, 2019). After winning the country’s first democratic elections in 1994, the African National Congress vowed to use land and agrarian reform to help reduce poverty, inequality and unemployment and roll back apartheid geography. Since 1997, a plethora of programmes have been implemented to advance this transformation agenda with little success. We review the major government-driven programmes implemented thus far and argue that the slow pace of reform is due mainly to underinvestment, constant chopping and changing of programmes between presidential terms and an overly-narrow focus on creating a class of black large-scale commercial farmers while neglecting millions of food-insecure blacks – especially women, many of whom already farm for subsistence - and as long as this persists, the clamour for land by blacks will only grow louder.